Circularly polarized inverted stacked high gain antenna with frequency selective surface. Issue 3 (March 2016) - Gangwar, Deepak; Das, Sushrut; Yadava, R.L.; Kanaujia, Binod Kumar
ABSTRACT: In this work; the novel design of dumbbell shaped frequency selective surface (FSS) is demonstrated as superstrate. The array of this designed FSS structure is incorporated on two different antennas; (1) Microstrip Patch Antenna (MPA), and (2) Inverted Stacked Microstrip Patch Antenna (ISMPA). The FSS unit cell reflection magnitude is nearly 0.95 in the vicinity of both antennas resonance frequencies. Based on the ray tracing phenomenon multiple reflections occur between superstate and ground plane. So by this phenomenon the gain of circular patch and the ISMPA is enhanced by 6.02 dBic and 5.1 dBic respectively. In the measured results, the impedance bandwidth of MPA and ISMPA are 6.66% (5.8–6.2 GHz) at 6 GHz center frequency and 5.3% (5.53–5.83 GHz) at 5.67 GHz center frequency respectively. The corner truncated dumbbell shaped FSS layer also acts as a polarizer. The axial ratio 3 dB band width of MPA and ISMPA are 8.66% (5.64–6.16 GHz) and 12.6% (5.52–6.24 GHz). Here simulation results are shown good agreement with measured results. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:732–740, 2016